Effect of Additives on Wood Pellet Physical and Thermal Characteristics: A Review. (14th February 2013) - Tarasov, Dmitry; Shahi, Chander; Leitch, Mathew
Abstract : Additives play a major role in wood pellet characteristics and are a subject of major interest as they act as binding agents for the biomass raw material. Past research has reported the use of lignosulphonate, dolomite, starches, potato flour and peel, and some motor and vegetable oils as additives for wood pellet production. This paper reviews the available research on the effect of different additives on wood pellets' physical and thermal characteristics. It was found that lignosulphonate and starch additives improve the mechanical durability but tend to reduce the calorific value of the wood pellets. Motor and vegetable oil additives increase the calorific value minimally but significantly increase carbon monoxide emissions. Corn starch and dolomite additives also significantly increase carbon monoxide emissions. In order to produce wood pellets with desired physical and thermal characteristics, a suitable additive with the right biomass material should be used.